Semi-synthetic salinomycin analogs exert cytotoxic activity against human colorectal cancer stem cells - Klose, Johannes; Volz, Claudia; Schmidt, Thomas; Schneider, Martin; Ulrich, Alexis (Biochemical and biophysical research communications, 2018)
Salinomycin, a polyether antibiotic, is a well-known inhibitor of human cancer stem cells. Chemical modification of the allylic C20 hydroxyl of salinomycin has enabled access to synthetic analogs that display increased cytotoxic activity compared to the native structure. The aim of this study was to investigate the activity of a cohort of C20-O-acyl analogs of salinomycin on human colorectal cancer cell lines in vitro. Two human colorectal cancer cell lines (SW480 and SW620) were exposed to three C20-O-acylated analogs and salinomycin. The impact of salinomycin and its analogs on tumor cell number, migration, cell death, and cancer stem cell specifity was analyzed. Exposure of human colorectal cancer cells to the C20-O-acylated analogs of salinomycin resulted in reduced tumor cell number and impaired tumor cell migration at lower concentrations than salinomycin. When used at higher (micromolar) concentrations, these effects were accompanied by induction of apoptotic cell death. Salinomycin analogs further expose improved activity against cancer stem cells compared to salinomycin.